Human APP Gene Expression Alters Active Zone Distribution and Spontaneous Neurotransmitter Release at the Drosophila Larval Neuromuscular Junction - Ekaterina A. Saburova; Alexander N. Vasiliev; Violetta V. Kravtsova; Elena V. Ryabova; Andrey L. Zefirov; Olga I. Bolshakova; Svetlana V. Sarantseva; Igor I. Krivoi (Neural Plasticity)
This study provides further insight into the molecular mechanisms that control neurotransmitter release. Experiments were performed on larval neuromuscular junctions of transgenic Drosophila melanogaster lines with different levels of human amyloid precursor protein (APP) production. To express human genes in motor neurons of Drosophila, the UAS-GAL4 system was used. Human APP gene expression increased the number of synaptic boutons per neuromuscular junction. The total number of active zones, detected by Bruchpilot protein puncta distribution, remained unchanged; however, the average number of active zones per bouton decreased. These disturbances were accompanied by a decrease in frequency of miniature excitatory junction potentials without alteration in random nature of spontaneous quantal release. Similar structural and functional changes were observed with co-overexpression of human APP and β-secretase genes. In Drosophila line with expression of human amyloid-β42 peptide itself, parameters analyzed did not differ from controls, suggesting the specificity of APP effects. These results confirm the involvement of APP in synaptogenesis and provide evidence to suggest that human APP overexpression specifically disturbs the structural and functional organization of active zone and results in altered Bruchpilot distribution and lowered probability of spontaneous neurotransmitter release.